A HAUNTOLOGICAL ANALYSIS OF DIGITAL MEMORIALIZATION OF THE DEAD - O'Connell, Carrie (AoIR Selected Papers of Internet Research, 2018)
Facebook now allows pages of the deceased to remain active, controlled by immediate family members of a deceased person, as a sort of memorialization or “electronic wake,” (Stokes, 2011). The overall goal of the author is to examine the evolution of the materiality of memorialization and investigate how our human connection with death has changed as our media tools have become untethered from tangible artefact. To explore the links between media, human relationships, and the spectral plane, and how those links might be revelatory in an age of digital media, a hauntological examination of these questions will be endeavored. The basic premise of hauntology, a clever merge of haunting and ontology derived by Jacques Derrida (1993), is that an idea, once tangibly realized and made real in the cultural zeitgeist, is never truly extinguished. Derrida’s hauntology derives from the ontological quest to articulate the nature of being, yet with the added perspective that everything that exists might not have ever lived, and nothing which is past ever really quite dies. This is no more so true than in our heavily mediated age in which written documents, photographs, film, and the Internet are able to capture, record, store—and, as will be discussed—even replicate beingness in physical form. In an age where simulacra parade as true being, and cultural memory of events as accepted historical provenance, perhaps a new perspective on the relationship between being and death is timely.